2021
DOI: 10.1186/s12935-021-02102-8
|View full text |Cite
|
Sign up to set email alerts
|

Gly-tRF enhances LCSC-like properties and promotes HCC cells migration by targeting NDFIP2

Abstract: Background Accumulating evidence demonstrates that tRFs (tRNA-derived small RNA fragments) and tiRNAs (tRNA-derived stress-induced RNA), an emerging category of regulatory RNA molecules derived from transfer RNAs (tRNAs), are dysregulated in in various human cancer types and play crucial roles. However, their roles and mechanisms in hepatocellular carcinoma (HCC) and liver cancer stem cells (LCSCs) are still unknown. Methods The expression of glyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Coincidentally, we note that Zhou et al's study 15 found that another tRF derived from tRNA‐Gly has a promoting effect on HCC cell migration by targeting NDFIP2. The sequence we researched (MINTbase‐ID: tRF‐22‐P4R8YP9LL) has a different source of mature tRNA than the Gly‐tRF in their article (MINTbase‐ID: tRF‐23‐PNR8YP9LD6).…”
Section: Discussionmentioning
confidence: 58%
“…Coincidentally, we note that Zhou et al's study 15 found that another tRF derived from tRNA‐Gly has a promoting effect on HCC cell migration by targeting NDFIP2. The sequence we researched (MINTbase‐ID: tRF‐22‐P4R8YP9LL) has a different source of mature tRNA than the Gly‐tRF in their article (MINTbase‐ID: tRF‐23‐PNR8YP9LD6).…”
Section: Discussionmentioning
confidence: 58%
“…Besides, plasma exosomal tRFs (tRNA-ValTAC-3, tRNAGlyTCC-5, tRNA-ValAAC-5 and tRNA-GluCTC-5) could serve as novel biomarkers for the diagnosis of liver cancer [ 156 ]. In terms of mechanisms, an HCC-upregulated tRF Gly-tRF enhanced liver cancer stem cell-like properties and promoted EMT by targeting NDFIP2 and activating the AKT signaling pathway [ 155 ]. In addition, Cho et al identified a distinct set of pre-tRNA 3’ trailer-derived tRFs by analyzing the profiles of small RNAs in Huh7 cells and human liver biopsies, which could sequester nuclear-cytoplasmic shuttling protein La/SSB in the cytoplasm by direct binding with their 3’U-tails, thus negatively regulating La/SSB-dependent viral gene expression [ 82 ].…”
Section: Biological Roles and Clinical Values Of Trfs In Cancermentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC), Gly-tRF targets Nedd4 family interacting protein 2 (NDFIP2) to promote the growth of HCC cells. Through analysis, NDFIP2 was found to regulate the AKT signaling pathway via ubiquitination of downstream target proteins, thereby regulating the malignant progression of HCC [ 87 ]. The expression of tRF-315 was increased in prostate cancer (PC) cells and could inhibit cisplatin-induced apoptosis.…”
Section: Dysregulation Of Tsrnas In Cancer and Related Rolesmentioning
confidence: 99%